ANALISIS PELAKSANAAN PRAKTIKUM MATA KULIAH BIOLOGI UMUM PROGRAM STUDI PENDIDIKAN MATEMATIKA IKIP PGRI PONTIANAK - Ivan Eldes Dafrita; Dwi Oktaviana (Buana Matematika : Jurnal Ilmiah Matematika dan Pendidikan Matematika, 2018)
The purpose of this study is to analyze whether there is a significant correlation between the practicum to final grade of the General Biology subject of Mathematics Education student IKIP PGRI Pontianak. Research subjects are all students of Mathematics Education which follow the subjects and practicum of General Biology starting from academic year 2014/2015 until 2016/2017. Instrument in this research is documentation of data result of practicum and final score of General Biology of academic year 2014/2015 until 2016/2017. Based on the result of research and discussion, it can be concluded that there is a significant correlation between the practicum to final score of the General Biology subject of Mathematics Education Student IKIP PGRI Pontianak for the academic year 2014/2015, 2015/2016, and 2016/2017 with the result of p value (Asymp Sig 2 tailed) of 0.000 is smaller than 0.05 Keywords: correlation, practicum, final score.